The relationship between novelty-seeking taits and comparative economic development - Erkan Gören (University of Oldenburg, Department of Economics, 2015)
This paper suggests a theoretical framework and provides empirical evidence for a hump-shaped relationship between the fraction of novelty-seeking traits in society and current levels of per capita income. The hypothesis is that novelty-seeking traits produce two countervailing effects on aggregate productivity and hence economic development. The beneficial effect consists in explorative knowledge acquisition, which contributes significantly to the process of economic development. The detrimental effect results from a certain amount of this knowledge not being used reliably for capital accumulation due to the high fraction of individuals engaged in exploration rather than in production. One main conclusion of the empirical analysis is that the high fraction of novelty-seeking individuals in society engaged in short-run explorative knowledge acquisition prevent permanent settlement and therefore act as an obstacle to the development of centralized states, which are a precursor to modern industrial production.
Keywords: N50; O10; O50; Z10; 330; Novelty-Seeking Behavior; Entrepreneurial Traits; Economic Development; Natural Selection; Genetic Diversity